2021
DOI: 10.3390/ijms22158005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Therapeutic Approaches to Prevent or Delay Post-Traumatic Osteoarthritis (PTOA) of the Knee Joint with a Focus on Sustained Delivery Approaches

Abstract: Inflammation plays a central role in the pathogenesis of knee PTOA after knee trauma. While a comprehensive therapy capable of preventing or delaying post-traumatic osteoarthritis (PTOA) progression after knee joint injury does not yet clinically exist, current literature suggests that certain aspects of early post-traumatic pathology of the knee joint may be prevented or delayed by anti-inflammatory therapeutic interventions. We discuss multifaceted therapeutic approaches that may be capable of effectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 240 publications
(409 reference statements)
0
28
0
11
Order By: Relevance
“…The possible reasons for this finding are multifactorial, including working status, early return to work because of economic factors, or poor compliance with physical therapy. Such patients may require more aggressive postoperative management approaches and follow-up protocols, including early detection of the progression of posttraumatic arthritis with serum biomarker levels [ 22 ], radiographic studies [ 23 ], prompt intervention with anti-inflammatory and regeneration therapy [ 24 ], aggressive rehabilitation programs for muscle strength around the knee joint, and adequate protective braces suitable for early return to work after ORIF.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons for this finding are multifactorial, including working status, early return to work because of economic factors, or poor compliance with physical therapy. Such patients may require more aggressive postoperative management approaches and follow-up protocols, including early detection of the progression of posttraumatic arthritis with serum biomarker levels [ 22 ], radiographic studies [ 23 ], prompt intervention with anti-inflammatory and regeneration therapy [ 24 ], aggressive rehabilitation programs for muscle strength around the knee joint, and adequate protective braces suitable for early return to work after ORIF.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied anti-inflammatory therapies in OA are inhibitors of IL-1, IL-6, and TNF-α. To date only a limited number of clinical trials have tested anti-inflammatory agents in human patients to impede PTOA of the knee ( 157 ). The only published trials are a proof-of-concept RCT using anakinra in 11 patients with an ACL rupture and a RCT using corticosteroid or placebo injection in 49 patients with an ACL injury.…”
Section: Future Anti-inflammatory Therapiesmentioning
confidence: 99%
“…Both RCT's reported on short-term patient reported outcomes and biomarkers with anakinra showing improvement in patient reported outcomes and corticosteroid injections showing improvements in some chondrodegenartive biomarkers ( 158 , 159 ). Multiple promising targets to counteract post-traumatic inflammation exist, leaving room for future clinical trials ( 157 ).…”
Section: Future Anti-inflammatory Therapiesmentioning
confidence: 99%
“…Competitive binding at the IL-1 receptor by IL-1RA is considered the primary action inhibiting the joint’s inflammatory process [ 7 , 9 ]. Studies have shown that IL-1RA prevents IL-1 ligand activation resulting in reduced synthesis of mediators such as metalloproteinases (MMPs), cyclooxygenase-2 (COX2), prostaglandins, and nitrous oxide that propagate OA [ 1 , 9 , 10 , 11 ]. Furthermore, the high concentration of IL-1RA in joints is crucial to maintain joint homeostasis whereas low levels are observed in synovial tissues from the OA patient [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using autologous bioactive agents enriched in anti-inflammatory mediators and growth factors for tissue regeneration has become a novel insight for OA management [ 11 , 23 ]. Apart from the IL-1 receptor modulation, several recent studies suggest that T cell-mediated response plays a significant role in the aggravation of OA, including an increase in activated T cells in synovial fluid and synovial membrane [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%